¿Cómo conceptuar la “Mística de la Pasión”? - Artola, C.P., Antonio M. (Alpha Omega, 2012)
The mystical theology of S. Paul of the Cross was defined by P. Marcel Viller as a ‘mystical theology of the Passion’, understood by the Saint as a sensitive infusion of the pains of Christ in the soul. But how can such an infusion of the pains of the ‘historical Christ’ be possible on the basis of his current status as ‘glorious’? How can a spiritual infusion be spiritual and, at the same time, sensitive? This is the problem addressed by this article.